2010
DOI: 10.1146/annurev.nutr.012809.104742
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Supply to the Human Fetus

Abstract: Deposition of fat in the fetus increases exponentially with gestational age, reaching its maximal rate-around 7 g/day or 90% of energy deposition-at term. In late pregnancy, many women consuming contemporary Western diets may not be able to meet the fetal demand for n-3 long chain polyunsaturated fatty acids (LCPUFAs) from the diet alone. Numerous mechanisms have evolved to protect human offspring from extreme variation or deficiency in the maternal diet during pregnancy. Maternal adipose tissue is an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
215
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(237 citation statements)
references
References 141 publications
(161 reference statements)
18
215
1
3
Order By: Relevance
“…The developing fetus requires substantial amounts of fatty acids to support rapid cellular growth and activity, and among these, the omega-3 polyunsaturated fatty acids (n-3 PUFAs) are particularly important (Haggarty 2010). Maternal dietary supplementation with n-3 PUFAs has beneficial effects on pregnancy outcomes, including increased gestation length (Szajewska et al 2006), reduced risk of pregnancy complications (Olsen et al 2000, Oken et al 2007, Zhou et al 2012, and increased fetal growth (Olsen et al 1990, Jones et al 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…The developing fetus requires substantial amounts of fatty acids to support rapid cellular growth and activity, and among these, the omega-3 polyunsaturated fatty acids (n-3 PUFAs) are particularly important (Haggarty 2010). Maternal dietary supplementation with n-3 PUFAs has beneficial effects on pregnancy outcomes, including increased gestation length (Szajewska et al 2006), reduced risk of pregnancy complications (Olsen et al 2000, Oken et al 2007, Zhou et al 2012, and increased fetal growth (Olsen et al 1990, Jones et al 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the AA are actively transported across the placenta to enter the fetal circulation to support fetal growth [14]. Lipids or fatty acids (FA) are released from placenta into the fetal circulation in the form of nonesterified fatty acids (NEFA) and are esterified in phospholipids by the fetal liver [15]. For this study, we used a subset of samples from a previously published fetal baboon study and analyzed AA, NEFA, and polar lipids (acylcarnitines and phospholipids).…”
mentioning
confidence: 99%
“…However, despite that the myelinogenesis process is not finished in fetus, the amount of trans isomers transferred to fetal brain was negligible in all studies. At least in animals, this finding suggests the brain might be protected from the trans fatty acids accumulation, but no data have yet been reported for human newborns (Haggarty, 2010).…”
Section: Effects Of Early and Prolonged Intake Of Hydrogenated Fat Fomentioning
confidence: 91%
“…How much the in utero environment dictates birth weight and the programming of long-term obesity related disorders is still unclear, especially when compared with that of early neonatal growth rate. The placental transfer of trans fatty acids is still contradictory, both in human and animals (Haggarty, 2010). However, experimental studies have demonstrated that placenta is not completely impermeable to these compounds, since a number of trans fatty acids cross this barrier and accumulates in the liver and in the total body lipids of the fetus.…”
Section: Effects Of Early and Prolonged Intake Of Hydrogenated Fat Fomentioning
confidence: 99%